Tennis-specific limitations in players with an ACL-deficient knee - Maquirriain, J. (Medicine and Science in Tennis, 2004)
The anterior cruciate ligament (ACL) is the most frequent completely disrupted ligament of the knee. Without treatment, this injury can lead to potentially debilitating consequences such as meniscus tears, anterior and rotational instability and early onset of osteoarthritis (6,10). Consequently, most orthopedic surgeons advocate surgical reconstruction of the ACL in patients who seek to return to athletic endeavors that depend on high functional demands on this ligament. However, demands of tennis movements on the ACL remain unknown and ACL insufficiency specific related to tennis players has received limited research interest with only few mentions in the sports medical literature. The aim of this prospective study was to identify tennis specific subjective limitations in players with a unilateral ACL-deficient knee.